EKSEKUSI TERHADAP OBJEK JAMINAN FIDUSIA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR.18/PUU-XVII/2019. - Darmiwati Darmiwati2021 (Fakultas Hukum Universitas Islam Indragiri, 2021)
Fiduciary is the transfer of ownership rights to an object on the basis of trust provided that the object whose ownership rights are transferred remains in the control of the owner of the object. In the implementation of fiduciary, the goods that are pledged remain in the power of the debtor. Fiduciary guarantees are security rights for movable objects, both tangible and intangible and immovable objects, especially buildings that cannot be encumbered with mortgage rights. The principle of the object of the fiduciary guarantee is the creditor's trust in the debtor. In the fiduciary guarantee law, if the debtor defaults, the object of the fiduciary guarantee will be handed over to the creditor for the purpose of fiduciary execution. The fiduciary guarantee law gives the creditor the right to carry out the execution of the fiduciary guarantee object, the existence of this power, the creditor can withdraw the fiduciary guarantee object by means of parate execution. However, with the Constitutional Court Decision Number 18/PUU-XVII/2019 regarding the application for judicial review of Article 15 section (2) and section (3), which requires a breach of contract agreement between the creditor and the debtor and the debtor's willingness to submit the object of collateral, has eliminated the rights of creditors and eliminated the principle of material rights. Based on these problems, the question in the research is how to execute the object of fiduciary security after the Constitutional Court Decision Number 18/PUU-XVII/2019 and what is the impact of the Constitutional Court Decision Number 18/PUU-XVII/2019. The legal research method in this paper is normative juridical which is reform oriented research. The conclusion in this study should be in the fiduciary guarantee certificate including the completeness of the default clause, to strengthen the evidence that the debtor has committed a breach of contract. If the debtor (fiduciary giver), after being agreed by the parties, is deemed to be in breach of contract (default), the execution of the object of the fiduciary guarantee can be carried out independently.